An aorto-oesophageal fistula treated with total arch repair combined with oesophageal repair. (15th February 2021) - Wang, Chaojie; Lei, Liming; Zhang, Wenqian; Fan, Xiaoping
Abstract: Aorto-oesophageal fistula is a rare but fatal disease. Open surgical repair or endotube repair of aorta and oesophagus save patients from circulatory deterioration, major haematemesis and severe infection. Here we present a rare case of an aorto-oesophageal fistula in the right hemi-arch caused by a fish bone treated with an alternative surgical strategy. Total aortic arch repair using the frozen elephant trunk procedure combined with oesophageal repair were performed. No aortic fistula, oesophageal fistula or artificial graft infection occurred in the follow-up.